Supplementation with porcine placenta extract reduces negative emotions and enhances positive emotions in healthy adults: a randomized, double-blind, placebo-controlled study - Naoya Morita; Eiichi Hirano (Frontiers in Nutrition)
BackgroundMental health conditions such as depression, anxiety, and stress represent significant global health challenges. According to the World Health Organization, there is an urgent need for safe and effective interventions to alleviate this burden. However, existing approaches to address these conditions remain insufficient. Placenta extract, obtained by enzymatic digestion of the placenta, has demonstrated efficacy in improving menopausal symptoms and may represent a novel interventional option.ObjectiveThis study aimed to evaluate the effects of porcine or equine placenta extract (pPE or ePE, respectively) intake on stress levels in healthy adults.MethodsThis was a 12-week, randomized, double-blind, placebo-controlled study (ClinicalTrials Identifier: UMIN000053020; https://center6.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000060483). This study was conducted among Japanese men and women aged 20–65 years with total mood disturbance (TMD) scores of 40–75, as assessed by the Profile of Mood States, 2nd Edition. The primary endpoint was TMD score, while secondary endpoints included fatigue, quality of life, sleep quality, autonomic function, and stress hormone levels.ResultsThe pPE group showed significant reductions in TMD scores and improvements in Anger-Hostility, Confusion-Bewilderment, Vigor-Activity, and Friendliness subscales compared to the placebo group. In contrast, no significant improvement in TMD was observed in the ePE group compared to the placebo group. No significant differences in the secondary endpoints were observed among any of the groups.ConclusionThese findings suggest that placenta extract intake may reduce negative emotions while promoting positive ones.Clinical review registrationhttps://center6.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000060483, identifier UMIN000053020.